2000
DOI: 10.1128/aem.66.9.4045-4049.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Growth and Acid Formation in a Bacillus subtilis Pyruvate Kinase Mutant

Abstract: Based on measurements and theoretical analyses, we identified deletion of pyruvate kinase (PYK) activity as a possible route for elimination of acid formation in Bacillus subtilis cultures grown on glucose minimal media. Evidence consistent with the attenuation of PYK flux has come from metabolic flux calculations, metabolic pool and enzymatic activity measurements, and a series of nuclear magnetic resonance experiments, all suggesting a nearly complete inhibition of PYK activity for glucose-citrate fed cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 27 publications
5
38
1
Order By: Relevance
“…3 and 4) indicates that attenuating PYK flux to a near-zero level may also be a fruitful starting point for enhancing folic acid production by B. subtilis. Moreover, controlling pyk activity at a low value via IPTG induction may overcome the low growth rate limitation of a pyk knockout (8). Overall, we found that when provided with a low level of IPTG (0.02 mM), an inducible pyk mutant, BSTZ0402, exhibits a threefold higher folic acid yield compared to the parent strain B. subtilis 168.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…3 and 4) indicates that attenuating PYK flux to a near-zero level may also be a fruitful starting point for enhancing folic acid production by B. subtilis. Moreover, controlling pyk activity at a low value via IPTG induction may overcome the low growth rate limitation of a pyk knockout (8). Overall, we found that when provided with a low level of IPTG (0.02 mM), an inducible pyk mutant, BSTZ0402, exhibits a threefold higher folic acid yield compared to the parent strain B. subtilis 168.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast, a pyk knockout of E. coli grows nearly as fast as the wild type (29). The difference in the growth rates of B. subtilis and E. coli can be attributed to different anaplerotic routes to oxaloacetate formation are used by the two species as was explained in a prior publication (8).…”
Section: Subtilis Engineering For Folic Acid Total Synthesis 7125mentioning
confidence: 86%
See 3 more Smart Citations